Physical performance in women´s football preseason. Body composition, heart rate and biomarkers, are they important? - Izquierdo Velasco, J. M.; de Benito Trigueros, A. M.; Delgado Márquez, E.; Redondo-Castán, J. C. (Revista Internacional de Ciencias del Deporte, 2022)
A well-designed football pre-season is crucial for the subsequent physical performance of the players. This study aimed to analyse, in this period, the effects of body composition, heart rate variability and physiological biomarkers on female football players` physical performance. To this end, 22 amateur female football players (23.68 ± 3.69 years) of the same team participated in the study. Physical performance factors (acceleration capacity and jumping ability), body composition, perceived exertion load, heart rate variability and some physiological biomarkers (salivary testosterone and cortisol) were evaluated weekly during a 5-week pre-season period (from T0 to T5). Wilks` Lambda indicated a significant F-value in all variables except the high and low heart frequency ratio (LFtoHF). Scheffe`s post-hoc identified differences between T0 and all weeks in anthropometry variables, and between T0 and T5 in all other variables. According to the regression analyses, it was revealed a negative impact between percentage of body fat and physical capacities, particularly with 20-m (-13.77) and 40-m (-14.46) when the exertion is measured by the logarithm of the root mean square of successive R-R interval differences (RMSSD). Therefore, the present research suggests that amateur female football players who start the training season with a lower body fat percentage are able to achieve a better fitness level in a short period of time.